Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Kurikulum Merdeka dalam Meningkatkan Pembentukan Karakter Peduli Lingkungan Siswa di MINU Waru 1 Sidoarjo - Nazilatul Auliyah; Nelud Darajaatul Aliyah; Solchan Ghozali (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The implementation of the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum is an effort to build student character by providing students with opportunities to gain knowledge through direct experience. This study aims to describe the implementation of Pancasila Student Profile Strengthening Project (P5) Independent Curriculum in improving the environmentally caring character of students at MINU Waru 1. Data collection techniques used interviews, observations and documentation. The results of the study indicate that the Pancasila Student Profile Strengthening Project (P5) can improve students' environmentally conscious character with the existence of recycling project activities and teacher strategies that are implemented can bring about changes in students' mindsets towards items that can pollute the environment, and increase students' awareness of the environment around them. The conclusion in this study, the Pancasila Student Profile Strengthening Project (P5) provides students with the opportunity to gain knowledge through direct experience so that it can improve students' environmentally conscious character.